Differences in forest plant functional trait distributions across land‐use and productivity gradients1. Issue 7 (1st July 2013) - Mayfield, Margaret M.; Dwyer, John M.; Chalmandrier, Loïc; Wells, Jessie A.; Bonser, Stephen P.; Catterall, Carla P.; DeClerck, Fabrice; Ding, Yi; Fraterrigo, Jennifer M.; Metcalfe, Daniel J.; Queiroz, Cibele; Vesk, Peter A.; et al.
Abstract : Premise of study: Plant functional traits are commonly used as proxies for plant responses to environmental challenges, yet few studies have explored how functional trait distributions differ across gradients of land‐use change. By comparing trait distributions in intact forests with those across land‐use change gradients, we can improve our understanding of the ways land‐use change alters the diversity and functioning of plant communities. Methods: We examined how the variation and distribution of trait values for seven plant functional traits differ between reference natural forest and three types of land‐use conversion (pasture, old‐field, or "legacy" sites—regrowth following logging), landscape productivity (NPP) and vegetation strata (tree or non‐tree "understory"), in a meta‐analysis of studies from 15 landscapes across five continents. Key results: Although trait variation often differed between land‐uses within a landscape, these patterns were rarely consistent across landscapes. The variance and distribution of traits were more likely to differ consistently between natural forest and land‐use conversion categories for understory (non‐tree) plants than for trees. Landscape productivity did not significantly alter the difference in trait variance between natural forest and land‐use conversion categories for any trait except dispersal. Conclusions: Our results suggest that even for traits well linked to plant environmental response strategies, broad classes of land‐use change and landscape productivity are not generally useful indicators of the mechanisms driving compositional changes in human‐modified forest systems.